Hedgie blasts off! - Brett, Jan, 1949- (Putnam, 2006)
When the spectacular, sparkling explosions at a popular tourist sight slow down, Hedgie the hedgehog is the only one capable of flying to tiny planet Mikkop to see what is wrong.